Correction: Functionalised type-I collagen as a hydrogel building block for bio-orthogonal tissue engineering applications. Issue 26 (20th June 2017) - Ravichandran, R.; Islam, M. M.; Alarcon, E. I.; Samanta, A.; Wang, S.; Lundström, P.; Hilborn, J.; Griffith, M.; Phopase, J.
Abstract : Correction for 'Functionalised type-I collagen as a hydrogel building block for bio-orthogonal tissue engineering applications' by R. Ravichandran et al., J. Mater. Chem. B, 2016, 4, 318–326.